Seismic damage model incorporating nonlinear effective energy dissipation and residual displacement for self-centering precast segmental bridge columns - Ruofan Gao; Yingjie Luo; Qinling Hong; Jingran He (Soil Dynamics and Earthquake Engineering, 2026)

Nano-sized titanium dioxide exposure induces non-hyperandrogenic polycystic ovarian syndrome in rats by increasing aromatase and apoptosis in granulosa cells - Weidong Zhou; Wenjing Zhang; Zhineng Fu; Chen Tang; Pengtao Chen; Ruofan Huang; Chunyan Yang; Shuzhen Chen; Zhenghong Zuo; Qionghua Chen; Mingyue Chen; Chengyong He (Journal of Environmental Sciences, 2025)

N-doped carbon featuring dual active sites of Fe3C and Fe0: Mechanisms for peroxydisulfate activation in nitrite removal - Ruofan Wu; Xu Zhai; Zhenli He; Xiaoe Yang (Journal of Environmental Management, 2025)

Research on the Coupling Dynamics Characteristics of Underwater Multi-Body Separation Considering the Influence of Elastic Constraints - Jiahui Chen; Yanhua Han; Ruofan Li; Zhenmin He; Yong Zhang (Journal of Marine Science and Engineering, 2025)
Based on the Newton–Euler method, a multi-body coupling dynamics model of the separation process of underwater vehicles is established. The conditions of contact and detachment between the sub-vehicle and each group of elastic gaskets are analyzed in detail, and the elastic gasket constraint model is established to simulate the elastic contact and detachment process. Based on the Computational Fluid Dynamics (CFD) method, the hydrodynamic data of vehicles under different cases is calculated. In this context, a relatively accurate hydrodynamic database is established, where the hydrodynamic of the Unmanned Underwater Vehicle (UUV) is obtained through fitting, while those of the sub-vehicles are calculated using online interpolation. These provide conditions for realizing Fluid–Structure Interaction (FSI) calculation. Utilizing the FSI simulation method in the multi-body separation process, the separation dynamics of the multi-vehicle under the influence of elastic constraint parameters are analyzed. The simulation results show that the pitching attitude angles of the UUV and sub-vehicle in the separation process are negatively correlated with the change of elastic constraint stiffness, and the load is positively correlated with it, which are in opposite optimization directions. When the total stiffness of the elastic gaskets remains constant, changes in the number of elastic gaskets have a minimal impact on the UUV and sub-vehicle motion state during separation, but significantly affects the load fluctuations on the sub-vehicle, leading to structural vibration issues. The analysis method established in this paper is capable of quickly assessing the safety of underwater vehicle separation for different elastic gasket schemes, thereby facilitating the optimization of parameters.

Sensitivity analysis of design parameters on the seismic performance of self-centering precast segmental bridge columns - Ruofan Gao; Yingjie Luo; Jingran He (Soil Dynamics and Earthquake Engineering, 2025)

Effect of long-term carbonation on strength and permeability of magnesia-coal based solid waste backfill materials - Wei He; Lang Liu; Zhiyu Fang; Baoning Wei; Qifeng Jia; Mengbo Zhu; Ruofan Wang; Huisheng Qu; Yuheng Gao; Lei Xia (Process Safety and Environmental Protection, 2025)

Understanding the impacts of street greening patterns and wind directions on the dispersion of fine particles - Xiaoping Chen; Jinyu He; Meng Han; Xuan Li; Ruofan Xu; Hang Ma; Xiaoshuang Wang; Xiaogang Wu; Prashant Kumar (Science of The Total Environment, 2024)

Automatic detection of Alzheimer’s disease from EEG signals using an improved AFS–GA hybrid algorithm - Ruofan Wang; Qiguang He; Lianshuan Shi; Yanqiu Che; Haojie Xu; Changzhi Song (Cognitive Neurodynamics, 2024)

The role of information industry convergence in energy transition - Ruofan He; Congwen Su; Sichen Liu (Journal of Environmental Management, 2024)

Zinc glycerolate (Glyzinc): A novel foliar fertilizer for zinc biofortification and cadmium reduction in wheat (Triticum aestivum L.) - Jiapan Lian; Liping Cheng; Xu Zhai; Ruofan Wu; Xiwei Huang; Dan Chen; Jianqing Pan; M.J.I. Shohag; Xiaoping Xin; Xinwei Ren; Zhenli He; Xiaoe Yang (Food Chemistry, 2023)